(untitled) (Bangladesh Journal of Otorhinolaryngology, 2013)
A 33-year-old male patient presented with left facial nerve palsy, left earache along with left ear bloody discharge for last 4 months. He also had left vocal cord paralysis and impairment of hearing on left side. Contrast enhanced computed tomography (CECT) of temporal bone revealed enhancing mass present in left middle ear and mastoid and also involving left temporal and occipital bone causing destruction of bone, mimicking as temporal bone malignancy. Complete excision of tumor was done and biopsy came out to be paraganglioma. Patient had been operated previously for similar lesion 8 years ago. Paraganglioma with such extensive involvement of bone is not reported in literature and hence we describe this case to distinguish it from temporal bone malignancy. The tumor was not functional clinically as well as biochemically. DOI: http://dx.doi.org/10.3329/bjo.v19i1.12150 Bangladesh J Otorhinolaryngol 2013; 19(1): 58-64